To the knowledge of the complex of species close to Ocypus nitens (Schrank, 1781) (Coleoptera: Staphylinidae: Staphylininae) - E.A. Khachikov (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2020)
A detailed study of a group of species closely related to Ocypus nitens (Schrank, 1781) is presented. The questions of morphological evolution, phylogeny and distribution of the species of this complex are considered. In morphological analysis we selected characters using an approach, which is known as “character weighting”. Cluster matrix analysis was implemented in “Cluster analysis” version 5.0.1, using the Chekanovsky-Sørensen similarity coefficient (qualitative); 18 characters were distinguished and transformed into a binary matrix. On the basis of this matrix, a dendrogram of morphological similarity was built. A “manual” phylogenetic analysis using the methods of cladism was applied to identify of phylogenetic relationships. Apomorphic position was identified for 12 characters, on the basis of which the cladogam was built. As a result, it was revealed that this group consists of two phylogenetic branches. One branch is represented by the species O. ponomarevorum Khachikov, 2013, another includes four groups of species: O. cerceticus (O. cerceticus Coiffait, 1964, O. svetlanae sp. n.), O. latens (O. latens Solodovnikov, 2000), O. nitens (O. nitens (Schrank, 1781)) and O. hochhuthi (O. hochhuthi Eppelsheim, 1878, O. nabozhenkoi Khachikov, 2005). The description of the new species Ocypus svetlanae sp. n., locally distributed in the western part of Abkhazia, is presented. The species is close to O. cerceticus from which it reliably differs in the details of structures of the endophallus, primarily in the absence of the basal lamina of monotillator of endophallus and in the somewhat more expanded and flattened triangular monotitillator. Ocypus cerceticus has the monotillator more elongated, slightly chitinized, at the base with the basal lamina that rises above the surface of the endophallus. In addition, the punctures of the abdominal punctation of O. svetlanae sp. n. merge into longitudinal oblique rows, while in O. cerceticus they are more uniform. Ocypus hochhuthi is recorded for the fauna of Russia (North Ossetia) for the first time